Instruktionen und Ordnungen der Stiftsherrschaft Klosterneuburg: Quellen zur Verwaltung sowie zur Land- und Forstwirtschaft einer geistlichen Grundherrschaft in der Frühen Neuzeit - Löffler, Josef (2021)
The present edition includes various legal texts (instructions and orders) that were used to regulate the administration, the economy, and the relationship between the lordship of the manor and the subjects of the Lower Austrian monastery of Klosterneuburg.